Compression of Bamboo Culm Subjected to Different Treatment Duration - Mohamad Amirul Fahmin Mat Noh; Mohd Nazrul Roslan (Progress in Engineering Application and Technology, 2021)
Bamboos belongs to the Bambusoideae subfamily of the Poaceae class that is a tall treelike grass. Bamboos are some of the world’s fastest growing plants. Natural fiber applications in garment industry are fewer compared to man-made synthetic fiber. Environmentally friendly bamboo fibers have good mechanical properties that make them suitable substitutes for conventional fibers. This paper investigated on the properties of Gigantochloa wrayi (Buluh beti) bamboo on compression strength by referring to ISO 22157 (compression test for bamboo culm). This study involved three different internodes of the bamboo that includes the basal part, middle part and top part of the bamboo. All of the part undergo process which is chemical treatment with different soaking time. The different duration of the bamboo treated in the chemical treatment is to investigate the effect of the time on the compression strength of the bamboo. Once the fiber had been treated, the fibers went to testing process in order to obtain the compression properties. From the result, basal part of the bamboo with 6 hour of treatment exhibited highest value of 5840.33N compare to others part and duration of treatment.